A SMART INTERVIEW SIMULATOR USING AI AVATARS AND REAL-TIME FEEDBACK MECHANISMS (AI AVATAR FOR INTERVIEW PREPRATION) - Sahani, KM Kajal; Khan, Mohammad Sahil; Khatwani, Sanchay; Gupta, Shubham; Dubey, Amit (International Journal of Engineering Technologies and Management Research, 2025)
An example of such a tool is an application founded on a 3D avatar that provides a simulated interview. Such a platform provides users with the opportunity to engage with a virtual interviewer within a secure setting. Throughout the interview, the system gives them immediate feedback and grades their performance. React.js, which is a very popular and used JavaScript library, builds a responsive and smooth user interface. OpenAI GPT-3, which is a very advanced language model, assists in providing natural questions and answers, thus making the interview look genuine. Three.js is used to render the 3D animated avatar, providing a visual and interactive experience. With the combination of all these tools, the website provides a content-filled experience that can assist users in preparing for actual interviews better. The AI interview tool is particularly helpful for job applicants, students, and working professionals. Live feedback corrects them in the process of practicing improvement on responses, body language, and demeanour. Rather than practicing with friends or reading off guides, the users get the hands-on practice in a simulated environment.